EFFICIENCY AND NEW TRENDS IN THE USE OF DIGITAL MARKETING TOOLS IN THE KASHKADARYA REGION - Ochilov Javlonbek Ismail son (Ecominds Press, 2025)
The article analyzes the application and effectiveness of digital marketing mechanisms for industrial enterprises in the Kashkadarya region. The main objective of the study is to determine how digital marketing tools are used by industrial enterprises in the region and assess their effectiveness. This analysis will help optimize digital marketing strategies for the industrial sector in the province. The results of the study show that many industrial enterprises in the Kashkadarya region are using digital marketing mechanisms only to a limited extent, and this is causing them to lag behind in market competition. Among the analyzed enterprises, the effectiveness of digital marketing strategies is also distinguished, while some enterprises have introduced advanced technologies, while others have difficulty doing so. The study also included a recommendation to increase the level of application of digital marketing mechanisms.
Keywords: Digital marketing, industrial enterprises, marketing mechanism, marketing strategies, Kashkadarya region, competitiveness, technological innovation, marketing analysis, digital transformation, efficiency.